Integrated metabolome and transcriptome analysis reveals salicylic acid and flavonoid pathways’ key roles in cabbage’s defense responses to Xanthomonas campestris pv. campestris - Sun, Qingguo; Xu, Zhongmin; Huang, Wei; Li, Dawei; Zeng, Qi; Chen, Lin; Li, Baohua; Zhang, Enhui (Frontiers in Plant Science, 2022)
Xanthomonas campestris pv. campestris (Xcc) is a vascular bacteria pathogen causing black rot in cabbage. Here, the resistance mechanisms of cabbage against Xcc infection were explored by integrated metabolome and transcriptome analysis. Pathogen perception, hormone metabolisms, sugar metabolisms, and phenylpropanoid metabolisms in cabbage were systemically re-programmed at both transcriptional and metabolic levels after Xcc infection. Notably, the salicylic acid (SA) metabolism pathway was highly enriched in resistant lines following Xcc infection, indicating that the SA metabolism pathway may positively regulate the resistance of Xcc. Moreover, we also validated our hypothesis by showing that the flavonoid pathway metabolites chlorogenic acid and caffeic acid could effectively inhibit the growth of Xcc. These findings provide valuable insights and resource datasets for further exploring Xcc–cabbage interactions and help uncover molecular breeding targets for black rot-resistant varieties in cabbage.